If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 32 + -4(x + -6) = -2 Reorder the terms: 32 + -4(-6 + x) = -2 32 + (-6 * -4 + x * -4) = -2 32 + (24 + -4x) = -2 Combine like terms: 32 + 24 = 56 56 + -4x = -2 Solving 56 + -4x = -2 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-56' to each side of the equation. 56 + -56 + -4x = -2 + -56 Combine like terms: 56 + -56 = 0 0 + -4x = -2 + -56 -4x = -2 + -56 Combine like terms: -2 + -56 = -58 -4x = -58 Divide each side by '-4'. x = 14.5 Simplifying x = 14.5
| t=9x+6 | | 2(4x+9)=16x+15-8x+3 | | 3x+18-17=41 | | 3(x+4)=8x+8-5x+4 | | 7(4x-3)=-6x+3(3+8x) | | 2(m+5)=5m+6-m | | (9x+2)(8x^2+7x+1)= | | 5x+2y=785+3280 | | -4n=1/3 | | 5-7x=24-14x | | x+4066=10546 | | -2(2+x)+4(1+8x)=8x+6x | | 4x^3-17x^2-4x=-2 | | 4-5x=-24 | | 8x+32x-6=10(4x+5) | | x+2+20x+100=0 | | 5x+2=-6 | | -2=4(0)+y | | 4x+12=-1088x | | w+1.9=5.56 | | 4x^3-17x^2-4x+2=0 | | 3x/4=-y | | -2=4x+0 | | 5+2y=-6 | | 36-(2c+4)=2(c+6)+c | | 15b+5b=960 | | -8(n+2)=-4(3n-2) | | x+2(0)=-2 | | x^3-8x^2+16x+957=0 | | x-20=-28 | | T=p+spfora | | 360+4x=(10+6)x |